Clinical significance of perioperative changes in ankle-brachial index with regard to extremity-related outcome in non-diabetic patients with critical limb ischemia - Bischoff, Moritz; Meisenbacher, Katrin; Peters, Andreas; Kronsteiner, Dorothea; Böckler, Dittmar (Langenbeck's archives of surgery, 2018)
PurposeTo evaluate the significance of perioperative changes in ankle-brachial index (ABI) with regard to extremity-related outcome in non-diabetic patients with critical limb ischemia (CLI) following revascularization.MethodsThe study represents a subanalysis of the multicentric Registry of First-line Treatment in Patients with CLI (CRITISCH). After exclusion of diabetic patients, conservative cases, and primary major amputation, 563 of 1200 CRITISCH patients (mean age 74 ± 10.7 years) were analyzed. This population was divided into two groups regarding perioperative ABI changes ∆ + 0.15 (Group 1) or ∆ − 0.15 (Group 2). Study endpoints were reintervention and major amputation during a mean follow-up of 14.6 ± 9 months. Logistic regression was performed in order to identify factors for ABI group affiliation.ResultsThere were 279 patients in Group 1 (49.5%) and 284 in Group 2 (51.5%). ABI sensitivity and specificity regarding vessel patency were calculated to be 54 and 87%. A preoperative ABI ≤ 0.4 [odds ratio (OR) 7.7], patent vessels at discharge (OR 12.2), and secondary interventions (OR 2.4) were identified as factors for Group 1 affiliation. Contrariwise, previous revascularization (OR 0.6), a glomerular filtration rate ≤ 15 ml/min/1.73 m2 (OR 0.3), and TASC A lesions (OR 0.2) were associated with Group 2 affiliation. No statistical difference was found with regard to the need of reintervention. However, time to reintervention was significantly shorter in Group 2 compared to that in Group 1 (10.0 ± 9.5 months vs 12.1 ± 9.1 months; p = 0.005). Amputation rate in Group 2 was 14.4%, significantly higher compared to that in Group 1 (6.0%; p < 0.0001).ConclusionsFailure of perioperative ABI improvement is associated with a higher probability for amputation and should be valued as prognostic factor in non-diabetic patients with CLI. Patients with no/marginal improvement in ABI after revascularization require close follow-up monitoring and may benefit from early reintervention.
Gesehen am 10.09.2019